2011
DOI: 10.3109/13651501.2011.593263
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between childhood trauma and borderline personality symptomatology in a consecutive sample of cardiac stress test patients

Abstract: In this non-psychiatric-treatment-seeking population, there appear to be relationships between various forms of trauma (especially sexual abuse) and borderline personality symptomatology, reinforcing the role of childhood trauma in borderline personality disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
24
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 19 publications
4
24
0
Order By: Relevance
“…These findings support the high rates of emotional dysregulation, indicated by low distress tolerance, characteristicly seen in BPD (Crowell et al 2009;Glenn and Klonsky 2009;Reeves et al 2010) and also support previous findings that alcohol use problems tend to be more typical of BPD than other types of personality disorders (Walter et al 2009;Zanarini et al 2010). Furthermore, given that a past experience of trauma is thought to be integral to the development of BPD (Pagura et al 2010;Sasone et al 2011), it is not surprising to see that PTSD scores were also only correlated with Cluster B scores. Interestingly, there was a tendency for all of the psychological variables, with the exception of psychological distress, to demonstrate stronger relationships with Cluster B scores than Cluster A and C scores, which is consistent with the biosocial developmental model of BPD and previous studies on BPD.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…These findings support the high rates of emotional dysregulation, indicated by low distress tolerance, characteristicly seen in BPD (Crowell et al 2009;Glenn and Klonsky 2009;Reeves et al 2010) and also support previous findings that alcohol use problems tend to be more typical of BPD than other types of personality disorders (Walter et al 2009;Zanarini et al 2010). Furthermore, given that a past experience of trauma is thought to be integral to the development of BPD (Pagura et al 2010;Sasone et al 2011), it is not surprising to see that PTSD scores were also only correlated with Cluster B scores. Interestingly, there was a tendency for all of the psychological variables, with the exception of psychological distress, to demonstrate stronger relationships with Cluster B scores than Cluster A and C scores, which is consistent with the biosocial developmental model of BPD and previous studies on BPD.…”
Section: Discussionsupporting
confidence: 80%
“…The experience of trauma and PTSD is very common among individuals with BPD and is thought to be integral to its development (Pagura et al 2010;Sasone et al 2011). Correspondingly, there is also evidence that suggests PTSD is associated with problem gambling, with a recent meta-analysis revealing that an average of 12.3 % of treatment-seeking problem gamblers met the diagnostic criteria for PTSD .…”
Section: Introductionmentioning
confidence: 95%
“…Emotional Satisfaction in People with Borderline Personality Research on this clinical outcome is relevant because several studies have reported that emotional satisfaction in people with BPD is directly associated with the perceived quality of one's romantic relationship [9,17,66] . Specifically, an 18-month follow-up study found that women with BPD were less likely to report emotional satisfaction than women without BPD at the end of the follow-up period [7] .…”
Section: Clinical Characteristics Of People With Borderline Personalimentioning
confidence: 99%
“…In addition, the current study expands on the findings of the RCT by demonstrating a reduction of symptoms in a diverse sample of children and adolescents who recently experienced and/or disclosed sexual abuse and received services in the CAC setting. This is significant given past research that has demonstrated the long-term deleterious impact of childhood sexual abuse (Katerndahl et al 2005;Sansone et al 2011). A significant difference in baseline child-reported traumatic stress symptom severity on the CPSS was found based on gender, with girls reporting higher symptom severity than boys.…”
Section: Discussionmentioning
confidence: 67%